ANALISIS PELAKSANAAN KEWAJIBAN ATAS PAJAK PENGHASILAN PASAL 21 PADA RUMAH SAKIT XYZ - anggreni, ni made tika; Noviari, Naniek (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2020)
The company as a tax cutter has a very large and important role for the government. The company as the income tax cutter must record the tax expense calculation of Article 21 Income Tax in accordance with the rules and procedures for calculating taxes and the results of which will be paid or reported. This study was conducted at XYZ Hospital. The purpose of this research is to analyze the implementation of the obligation for income tax article 21 whether it is in accordance with the Act. This study uses qualitative research methods, with a case study approach method. The data used are employee salary data and reporting of PPH 21 period XYZ Hospital in 2017. The results of this study indicate that the calculations performed by XYZ Hospital are correct, but for the depositing and reporting of Article 21 Income Tax that has been applied by XYZ Hospital yet in accordance with the Act so that it causes the existence of contingency obligations that must be repaid.